Equivalency Education: Distance Learning and Its Impact in Indonesia - Arbarini, Mintarsih; Rahmat, Abdul; Ismaniar, Ismaniar; Isa, Abd Hamid; Siswanto, Yudi (Journal of Nonformal Education, 2022)
Education underwent changes during the emergency period of Covid-19 spread, including Equivalency education in taking measures in response to and anticipation of Covid-19 spread, not having face-to-face learning activity, and changing to online learning. This research aimed to examine the impact of distance/online learning on Equivalency education in Indonesia. This research used quantitative method and survey approach to collect information of distance learning in equivalency education. The respondents were tutors and students of package A, package B, and package C in Sumatra Island, Java Island, and Nusa Tenggara. The research sample consisted of 129 equivalency tutors and 148 equivalence students. The data were collected via online questionnaire. The data were analyzed using descriptive statistics by presenting the frequency distribution. The research results show that the preparation for distance learning in the facilities and infrastructures aspects in support of learning was not optimal, as shown with low-power and uneven internet network. The learning components were prepared based on the standard determined by tutors themselves referring to the curriculum. The ability of using learning information technology was still a problem because of low digital literacy. Learning was carried out through various platforms of learning management system and social media and the seTara Daring platform prepared by the ministry of education was not used for uniformity of distance/online learning. Assignment was dominant in the learning method. Learning evaluation was carried out through presentation, questions and answers, practice, daily quiz, mid-term exam, and final exam. The inconsistent connectivity between teachers, students, and parents led to students’ affective achievement not in line with learning objective. Therefore, improvement is needed in the implementation of distance/online learning covering improved facilities, application with user friendly platforms, and efficient, continuous and integrative online socialization.